Supporting self-care for eczema: protocol for two randomised controlled trials of ECO (Eczema Care Online) interventions for young people and parents/carers. Issue 2 (5th February 2021) - Muller, Ingrid; Stuart, Beth; Sach, Tracey; Hooper, Julie; Wilczynska, Sylvia; Steele, Mary; Greenwell, Kate; Sivyer, Katy; Yardley, Lucy; Williams, Hywel C; Chalmers, Joanne R; Leighton, Paul; et al.
Abstract : Introduction: Eczema care requires management of triggers and various treatments. We developed two online behavioural interventions to support eczema care called ECO (Eczema Care Online) for young people and ECO for families. This protocol describes two randomised controlled trials (RCTs) aimed to evaluate clinical and cost-effectiveness of the two interventions. Methods and analysis: Design : Two independent, pragmatic, unmasked, parallel group RCTs with internal pilots and nested health economic and process evaluation studies. Setting : Participants will be recruited from general practitioner practices in England. Participants : Young people aged 13–25 years with eczema and parents and carers of children aged 0–12 years with eczema, excluding inactive or very mild eczema (five or less on Patient-Oriented Eczema Measure (POEM)). Interventions : Participants will be randomised to online intervention plus usual care or to usual eczema care alone. Outcome measures : Primary outcome is eczema severity over 24 weeks measured by POEM. Secondary outcomes include POEM 4-weekly for 52 weeks, quality of life, eczema control, itch intensity (young people only), patient enablement, health service and treatment use. Process measures include treatment adherence, barriers to adherence and intervention usage. Our sample sizes of 303 participants per trial are powered to detect a group difference of 2.5 (SD 6.5) in monthly POEM scores over 24 weeks (significance 0.05, power 0.9), allowing for 20% loss to follow-up. Cost-effectiveness analysis will be from a National Health Service and personal social service perspective. Qualitative and quantitative process evaluation will help understand the mechanisms of action and participant experiences and inform implementation. Ethics and dissemination: The study has been approved by South Central Oxford A Research Ethics Committee (19/SC/0351). Recruitment is ongoing, and follow-up will be completed by mid-2022. Findings will be disseminated to participants, the public, dermatology and primary care journals, and policy makers. Trial registration number: ISRCTN79282252 .